A new species of Phymaturus of the patagonicus clade (Squamata, Liolaemidae) from isolated plateau of southwestern Rio Negro Province, Argentina - Scolaro, Jose Alejandro (2012)
A new Phymaturus species called Phymaturus sinervoi, is described in the present study. The new species is a member ofthe “Phymaturus patagonicus” group from Patagonia. It lives at about 1100 m of altitude in a volcanic rocky habitat nearto Cari Laufquen plateau, in the southern-central steppe of Rio Negro Province, Argentina. The new species and the neigh-bouring related species of the genus from the “patagonicus” group are morphologically compared, and its distribution and natural history are pointed out.